Japanese kanji for beginners : (JLPT Levels N5 & N4) first steps to learning the basic Japanese characters [Includes Printable Flash Cards]. - Stout, Timothy G. (Tuttle Publishing, 2017)
This handy book teaches you a new mnemonics-based method to read and write the 430 highest-frequency kanji characters. The accompanying CD-ROM includes an interactive game, printable flash cards, and native-speaker audio recordings of all 430 kanji and their related vocabulary.